The Influence of Cutting Age and Liquid Organic Fertilizer Dosage on The Yield of King Grass (Pennisetum purpupoides Schumach) as Source of Livestock - Yunida Berliana; Juli Mutiara Sihombing; Khairani Khairani; Erfan Wahyudi (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2021)
Introduction: Grasses is one part of the forage, that it is necessary to support the production of grass management. The research was to determine the effect of cutting age and the use of liquid organic fertilizers (LOF) for king grass in overcoming the problem of forage feed availability. Materials and Methods: This research was conducted at the experimental field in Faculty of Agriculture and Animal Husbandry, Universitas Tjut Nyak Dhien, Medan Tuntungan Subdistrict, North Sumatra. This research used a split plot design with two factors. The main-plot was the cutting age, include T1= 35 days; T2= 45 days; T3= 55 days. The sub-plot was the different dosage of LOF, such as P0= un-fertilization; P1= 50 l.ha-1; P2= 75 l.ha-1; P3= 100 l.ha-1. The parameters were analyzed the F-test and continued with the LSD at level of 5%. Results: The cutting age significantly increased the tillers, yield of fresh matter, yield of dry matter, and storage capacity, but it had insignificant effect on the height of king grass with the highest increase was at the age of 55 days. The LOF doses significantly increased the height of king grass, tillers, and yield of fresh matter with the highest increase at the dose of 100 l.ha-1, but it had insignificant effect on yield of dry matter and storage capacity. Interaction between the cutting age with LOF significantly increase the highest of king grass height at 100 l.ha-1 of LOF + 55 days of 220.67 cm.